The Relationship of Water and Sanitation with the Incidence of Stunting: A Bibliometric Analysis - Yuniarti, Elsa; Azzahra, Nabila; Nugraha, Fitra Arya Dwi (Gema Lingkungan Kesehatan, 2025)
This research analyzes trends in studies regarding the relationship between water, sanitation, and stunting in children under five through bibliometric analysis. Water, sanitation, and hygiene (WASH) interventions are recognized as critical factors in addressing childhood stunting, yet the research landscape remains fragmented across disciplines. A total of 130 publications from the Scopus database covering 2010-2024 were analyzed using VOSViewer software. Co-occurrence analysis, co-authorship analysis, and citation analysis were performed to identify research patterns, collaboration networks, and knowledge clusters. The results reveal that medical sciences dominate the field (34.6%), followed by nursing (15.4%) and environmental sciences (13.8%), with research articles comprising 77.2% of publications. The United States leads in publication output with 35 documents, while Johns Hopkins Bloomberg School of Public Health emerges as the most prolific institution with 8 publications. Publication trends show significant growth from 2010 to 2020, peaking at 23 publications in 2020. International collaboration analysis demonstrates strong cooperation networks, particularly between the United States and the United Kingdom. Keyword co-occurrence analysis identified three distinct clusters: Cluster 1 focusing on growth disorders and child development, Cluster 2 emphasizing stunting epidemiology and risk factors, and Cluster 3 addressing WASH interventions and pathogen exposure. The research landscape reveals disciplinary fragmentation that may explain contradictory findings and limited intervention effectiveness. Enhanced interdisciplinary collaboration and integration of clinical, epidemiological, and intervention perspectives are essential for developing comprehensive stunting prevention strategies, particularly in low- and middle-income countries.